Mechanisms of Ecological Adaptation of Rare Fish Species in the Conditions of the Khorezm Oasis - Khushnutovna, Babadjanova Sayyora (American Journal of Biology and Natural Sciences, 2026)
The Khorezm oasis is located in the lower reaches of the Amu Darya basin and is a complex hydro-ecological region, characterized by instability of the hydrological regime, a high degree of water salinity, and increased anthropogenic pressure. These factors have a significant impact on the composition of aquatic ecosystems and ichthyofauna in the region, especially on the distribution and stability of rare and environmentally vulnerable fish species.